Механизмы деления пластид и их разнообразие - Бова, Д.А.; Костиков, И.Ю. (Альгология, 2011)
Приведен анализ литературных данных о б аппарате и молекулярных механизмах деления пластид у фотоавтотрофных организмов различных фил. Обсуждаются аппараты деления клетки у эвбактерий (включая цианопрокариот), у первично- и вторично-симбиотических пластид водорослей и высших растений различных отделов, а также простейших из типа Apicomplexa. Рассматриваются три типа деления пластид, условно определенные как прокариотический ( Glaucocystophyta), смешанный прокариотно-эвкариотический (прочие отделы во дорослей и высших растений) и эвкариотический (Apicomplexa). Обсуждаются принципы позиционирования, сборки, структуры и работы дивисомы и PDF-системы (Plastid-dividing, Dynamin, and FtsZ rings), локализация, функции и взаимодействия белков, вовлеченных в деление пластид различных типов, происхождение различных компонентов аппарата деления данного компартмента. Review deals with the analysis of literature data about molecular me chanisms and apparatuses of plastid division in photoautotrophic organisms of different phyla. Division apparatuses of eubacteria (including cyanobacteria), primary and secondary plastids of algae and land plants as well as of apicomplexans are discussed. Three types of plastid division defined as prokaryotic (Glaucocystophyta), mixed prokaryotic-eukaryotic (all other algae and land plants) and eukaryotic ( Apicomplexa) are reviewed. The principles of positioning, assembly, structure and functioning of the d ivisome and PDF (Plastid-dividing, Dynamin, and FtsZ rings) system are discussed. We reviewed localizations, functions and interactions of proteins involved in the division of bacteria and the different types of plastids. Furthermore, we discussed the evolutionary origin of the different components of plastid division apparatuses.